Research on Identification of Land Damage Types and Analysis of Damage Process in Opencast Coal Mine of Steppe - Jiancheng Yan; Yong Liu; Junhai Gao (E3S Web of Conferences, 2020)
Aiming at the situation of land damage caused by large Opencast Coal Mine in steppe, this paper took Borshil Opencast Coal Mine in Hulunbuir as the research object, identified the types of land damage caused by Opencast Coal Mine in the last 20 years, analysed the space-time sequence and quantity of land damage process, and calculated the coefficient of land damage based on the types of damage. We found that, since 1998 to 2018, the area of land improper excavation and land cover occupation increased year by year in Borshil Opencast Coal Mine, the area of land improper excavation changed inconspicuously between years, and the area of land cover occupation decreased between years; the area of land occupation increased first and then remained unchanged basically, and the proportion decreased from 36.5% to 16.2%. By 2018, the total area of land damage in Borshil Opencast Coal Mine was 5150.52 hm2, and the ratio of land improper excavation to land cover occupation to land piled up was about 3:5:2. In addition, the land damage coefficient of Borshil Opencast Coal Mine increased first and then decreased, reaching the maximum of 0.6425 hm2/104t in 2011, and it was 0.196hm2/104t in 1998-2018. The data combined with coal mine output can predict the future land damage area of mining area, and provide data support for land reclamation potential survey. It can also provide reference for the implementation of relevant national policies and plans.